Publication evaluation in the humanities: Necessary changes against inadequate indicators - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2017)
This paper argues the need to adapt the publication evaluation systems to the characteristics of the humanities, in order to overcome the current discrimination of these disciplines. Citation indicators applied to 2, 3, or 5 years of publication provide poor and distorted statistics for journal evaluation. The citation period should be extended and the classification system refined. On the other hand, it is essential to strengthen the incipient sources about monograph quality and publication modality with a central weight in the humanities.
Keywords: Humanities; Journal evaluation; Monographs evaluation; Bibliometric indicators; Impact factor.